HISTORICAL EVOLUTION AND FUNCTIONAL TRANSFORMATIONS OF MUSEUM INSTITUTIONS DURING THE SOVIET PERIOD (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article analyzes the formation of museum work in the Soviet period, the concept and development trends of museology, the policy of museology, and the institutional characteristics of cultural and educational activities.